KONSTRUKSI REALITAS PEMBERITAAN MANUVER POLITIK SURYA PALOH PADA MAJALAH GATRA DAN TEMPO - Rina Sovianti; Saeful Mujab; Erita Riski Putri (Fakultas Komunikasi, Sastra, dan Bahasa, 2021)
Surya Paloh's political maneuver in Gatra Magazine and Tempo discussed the Surya Paloh maneuver problem that was framed by Gatra and Tempo Magazine. Media and journalists need to be independent and objective in reporting news. However, receiving the latest news about getting the same news but containing several versions of the news. Certain media reported an event with one particular aspect or side of the news. Meanwhile, the media are preaching a different side of the news. The diversity of this version of the news shows that behind the greatness of the journalists in promoting independent and objective aspects, there are still other sides besides interests, ideology, politics, economics, society, culture, religion, and others. In other words, there is still a background of good or weak journalists in reporting something that cannot be separated from the news. Based on this background, it is interesting to discuss the Construction Reality of Surya Paloh's Political Maneuver in Gatra and Tempo Magazine. By using qualitative and descriptive methods, and using Robert N Entman's framing analysis method to analyze data, the results of this study will be valid and interesting.